(untitled) (Innovative professional education, 2024)
The subsection analyses the demand for and quality of vocational education, describes the specifics of vocational education in the context of lifelong learning and development, justifies the feasibility of using innovative educational practices, forms and methods of work; examines the implementation of projects within a vocational education institution, and considers the functioning of courses based on an educational institution for the purpose of training different groups of people by profession and age.